NEURO PROTECTIVE EFFECT OF LYCOPENE AND Tetracarpidium conophorum EXTRACTS ON HEAT-STRESSED COCKERELS: effect of herbal supplements on brain performance in heat-stressed cockerels - Ojo, Olayinka (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
The study was conducted to determine the neuro protective potential of lycopene and Tetracarpidium conophorum leave Extract (TCLE) on acetylcholinesterase activity and oxidative status of heat-stress cockerels. 25-week old cockerels (n=54) were used for this experiment. There were nine treatments: 0 ml of extract/ 250 ml of water (control)(T1), 30 ml of lycopene/250 ml of water (T2), 60 ml of lycopene/250 ml of water (T3), 30 ml of TCLE/250 ml of water (T4), 60 ml of TCLE /250 ml of water (T5), 15 ml of lycopene + 15 ml of TCLE/250 ml of water (T6), 30 ml of lycopene + 30 ml of TCLE/ 250 ml of water (T7), Vitamin C 0.1g/250 ml of water (T8), Cooler temperature (25±2oC) + Cold water 4oC (T9). Total Protein (TP), brain antioxdant; superoxide peroxidase (SOD), catalase (CAT), Glutathione peroxidase (GPx), Glutathiones-S transferase (GST), Glutathione (GSH), Malondialdehyde (MDA) Acetylcholinesterase (AChe) and phytochemical quantitative/ qualitative analysis of TCLE were evaluated. Results showed that value obtained for crude protein, moisture, ash and crude fibre content of TCL were depressed, while carbohydrate value was elevated. Also TCLE contain essential compounds as saponin, tannin, phenolics, flavonoids, alkaloids, steroids, glycosides, coumarins, triterpenes, terpenoids and fixed oils. There was non-significant effect (P>0.05) of lycopene and Tetracarpidium conophorum on TP, MDA and catalase of cockerel brain, however,brain GST, GPx, GSH, SOD and Acetylcholinesterase activities were significantly (P<0.05) influenced by the treatments. It was observed that the experimental inclusions did not significantly impose any negative effect on the cockerels.